2010
DOI: 10.1352/1934-9556-48.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Social Integration in Employment Settings: Application of Intergroup Contact Theory

Abstract: This study used a survey of 106 employment specialists to test the ability of intergroup contact theory to explain social integration outcomes of employees with disabilities. Contact theory suggests that coworkers are more accepting of employees with disabilities if they have sufficient opportunities to interact with them, equal status and interdependent working relationships, and supervisors who support equality and acceptance. The contact model and an expanded model that includes workplace culture significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…Similarly for adults, Fichten et al (2005) determined that individuals who volunteered with children with disabilities experienced less discomfort around individuals with disabilities, while individuals who had casual experiences with individuals with disabilities did not have more positive attitudes (Hampton and Xiao 2007). When the job situations of individuals with disabilities closely approximated the optimal conditions of contact described by Allport, individuals with disabilities were more likely to be socially integrated at work (Novak et al 2011), which improved the attitudes of coworkers without disabilities (Novak and Rogan 2010).Finally, Barr and Bracchitta (2012) determined that the type of relationship a person has with an individual with a disability is associated with positive attitudes more so than mere contact with such individuals.…”
Section: Attitudes Toward Individuals With Disabilitiesmentioning
confidence: 83%
“…Similarly for adults, Fichten et al (2005) determined that individuals who volunteered with children with disabilities experienced less discomfort around individuals with disabilities, while individuals who had casual experiences with individuals with disabilities did not have more positive attitudes (Hampton and Xiao 2007). When the job situations of individuals with disabilities closely approximated the optimal conditions of contact described by Allport, individuals with disabilities were more likely to be socially integrated at work (Novak et al 2011), which improved the attitudes of coworkers without disabilities (Novak and Rogan 2010).Finally, Barr and Bracchitta (2012) determined that the type of relationship a person has with an individual with a disability is associated with positive attitudes more so than mere contact with such individuals.…”
Section: Attitudes Toward Individuals With Disabilitiesmentioning
confidence: 83%
“…Because family, school, and employment-support systems and staff are critical during the employment journey, other factors, such as positive previous work experiences, supportive work environments, and social integration with coworkers, likely play a role as well (Carter & Ditchman, 2010;Novack & Rogan, 2010). These factors often come up against barriers, such as inaccessible transportation and perceived family concerns about safety and longterm placement of the individual (Migliore, Grossi, Mank, & Rigan, 2008).…”
mentioning
confidence: 99%
“…They found that workers with disabilities tended to be less fully included in workplace cultures than workers without disabilities, and that the inclusion tended to be higher in workplaces with stronger cultures. In another study of individuals with developmental disabilities, Novak and Rogan (2010) studied workplace culture as one of the "conditions of contact" (p. 46) for employees with disabilities, and found that employees in what they characterized as positive organizational cultures were more likely to interact socially with coworkers and their coworkers were more accepting of employees with disabilities.…”
Section: Research-article2014mentioning
confidence: 99%